Self-Assembly System Based on Cyclodextrin for Targeted Delivery of Cannabidiol - Zhu, Panyong; Lv, Pin; Zhang, Yazhou; Liao, Rongqiang; Liu, Jing; Guo, Rong; Chen, Xuan; Liao, Xiali; Gao, Chuanzhu; Zhang, Kun; Yang, Ming; Yang, Bo (Frontiers in Chemistry, 2021)
Cannabidiol (CBD) is one specific kind of the cannabinoid in Cannabis sativa L with a wide range of pharmacological activities. However, the poor water solubility and specificity of CBD limits its application in pharmaceutical field. For solving these problems, in this work, we successfully prepared a targeted carrier by grafting biotin (BIO) onto ethylenediamine-β-Cyclodextrin (EN-CD) in a single step to generate a functionalized supramolecule, named BIO-CD. Subsequently, an amantadine-conjugated cannabinoids (AD-CBD) was prepared and self-assembled with the BIO-CD. A series of methods were used to characterize the inclusion behavior and physicochemical properties of AD-CBD and BIO-CD. The results showed that AD-CBD entered the cavity of BIO-CD and formed a 1:1 host-guest inclusion complex. MTT assay and confocal laser scanning microscopy (CLSM) revealed that the targeting effect and anticancer activity of AD-CBD/BIO-CD inclusion complex against three human cancer cell lines were higher than BIO-CD, AD-CBD and free CBD. Moreover, the inclusion complex could release drugs under weakly acidic conditions. These results demonstrated that AD-CBD/BIO-CD inclusion complex possess excellent targeted and anticancer activity, which is hopeful to be applied in clinic as a new therapeutic approach.